2020
DOI: 10.18332/tpc/127523
|View full text |Cite
|
Sign up to set email alerts
|

Variation in characteristics of people with mental disorders across smoking status in the Canadian general population

Abstract: INTRODUCTION People with mental disorders are less successful in smoking cessation efforts. This study compared the characteristics of current smokers and former smokers with mental disorders. METHODS This was a cross-sectional study that used the Public Use Microdata File of the Canadian Community Health Survey 2012. Survey respondents with any mental health disorder in the last 12 months (n=2700), identified using the World Health Organization Composite International Diagnostic Interview instrument, were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…[7,8] Mental illness is also associated with social deprivation. The association between persistent smoking and social deprivation found by Odendaal et al [1] is similar to that found in Canada among PWMI, [9] and is consistent with the well-documented mental health/poverty cycle [10] (related to social exclusion as well as social and/or occupational impairment).…”
Section: Mental Illness: South Africa's Blind Spotsupporting
confidence: 85%
“…[7,8] Mental illness is also associated with social deprivation. The association between persistent smoking and social deprivation found by Odendaal et al [1] is similar to that found in Canada among PWMI, [9] and is consistent with the well-documented mental health/poverty cycle [10] (related to social exclusion as well as social and/or occupational impairment).…”
Section: Mental Illness: South Africa's Blind Spotsupporting
confidence: 85%